Analysis of The Influence of Digital Marketing And Brand Image on The Interest of Generation Z in Investing in Gold in Islamic Financial Institutions - Indriyani, Heny; Syahbudi, Muhammad; Nurwani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the role of digital marketing and brand image on Generation Z's interest in investing in digital gold through digital-based Islamic Financial Institutions, with a case study on Sharia Banking students at UIN Sumatera Utara Medan. The research method used is Partial Least Square Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. Data were collected through questionnaires distributed to students as research samples. The analysis results show that both variables—digital marketing and brand image—have a significant and positive influence on interest in digital gold investment. The research model is able to explain 82.2% of the variation in Generation Z's interest in digital gold investment. These findings indicate that strengthening brand image and implementing effective digital marketing strategies are crucial to increasing digital gold investment interest among students. The practical implication of this research is that Islamic financial institutions need to optimize digital marketing and build a strong brand image to attract young investors.